แนวปฏิบัติทางด้านกฎหมายการนำเข้าสินค้าของประเทศคู่ค้าและการพัฒนาผลิตภัณฑ์ ฮาลาลของไทยเพื่อการส่งออกในกลุ่มประเทศอาเซียน: กรณีศึกษาการส่งออกผลิตภัณฑ์ เครื่องแกงสำเร็จรูปไปประเทศบรูไนดารุสซาลาม - อัสมัน แตอาลี (2023)
This research's objectives are to: (1) study and compile legal practice guidelines, regulatory and legal information related to trade and investment in Brunei; (2) survey the demand for Thai instant curry in Brunei and the import route of Brunei; (3) study the guidelines for exporting instant curry paste to the community enterprise entrepreneurs in the 5 southern border provinces, the private sector, and the government to have an opportunity to jointly invest with Brunei and (4) make policy recommendations regarding investment in halal food, instant curry in the southern border provinces of Thailand, for export to markets outside ASEAN The researcher uses a mixed method, focusing on quality research rather than quantitative methods. It consists of document research in-depth interview and using questionnaires, by determining the population and sample, specifying the sample size, data collection methods and tools were used to collect data, plus research procedure and data analysis methods. The research results can be summarized as follows: 1. Regulations of exports and imports curry paste operators must register as customs clearance practitioners, to import the data into the computer system of the Customs Department. 2. Demand for Thai curry to the Brunei people found that Brunei people buy Thai curry to cook at home at the greater and highest levels. 3. Results of the taste test of different curry products indicate that for the curry products from Somjai Nueam Community Enterprise, coconut milk curry products and green curry paste products of Ban Ta Curry Community Enterprise, the sample group gave preference scores from moderate to very like level. 4. Directions for investing in instant curry paste between Brunei investors and community enterprises in 5 southern border provinces are 3 ways: 4.1 Model A: Invest with Bruneian Distributors 4.2 Model B: Doing OEM with Bruneian Company 4.3 Model C: Foreign Direct Investment 4.30%.